Spatiotemporal Variation and Risk Assessment of Pesticides in Water of the Lower Catchment Basin of Acheloos River, Western Greece. (28th December 2013) - Stamatis, Nikolaos; Hela, Dimitra; Triantafyllidis, Vassilios; Konstantinou, Ioannis
Abstract : A three-year monitoring survey (March 2005–February 2008) was conducted to investigate, on monthly basis, the presence of thirty pesticides belonging to various categories and metabolites, in Acheloos River (Western Greece), one of the most important water resources in Greece. Six sampling stations along the river were established. Water analyses were performed using solid-phase extraction combined with gas chromatography with flame thermionic detector and mass spectrometry. Statistical analysis using one-way ANOVA and Duncan's multiple range test (P < 0.05 ) was used to compare annual mean concentrations of pesticides, seasonal and spatial distribution. In general, the highest mean concentrations of the pesticides were recorded at the three stations downstream. The greatest average concentrations were determined during spring and summer in agreement with the pesticide application period. The observed lower concentrations after 2006 reflect the land-use change because of the elimination of tobacco, the main cultivation of the area for many decades. The compounds most frequently detected were diazinon (78.6%), DEA (69.3%), and fenthion (52.6%). Environmental risk assessment using risk quotient (RQ) approach showed high risk for six insecticides in 2005 and one in 2007. A compliance with the European Environmental Quality Standards (EQS) was observed for the priority pesticides.